THE EFFECTIVENESS OF THE KOPI PAHIT APPLICATION IN STUNTING PREVENTION EFFORTS IN THE PORONG COMMUNITY HEALTH CENTER WORK AREA - Abiyyah, Eka Azhar; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Stunting is a serious problem in health development in Indonesia because it impacts the quality of future human resources. This study aims to analyze the effectiveness of the KOPI PAHIT (Porong Innovation Complications to Prevent and Overcome Stunting) application as a digital innovation in stunting prevention efforts in the Porong Community Health Center (Puskesmas) work area, Sidoarjo Regency. This application is a digital innovation developed to support monitoring of the nutritional and health status of toddlers, as well as improve education for parents and integrated health post (Posyandu) cadres. Method: This study employed a descriptive qualitative method, with data collection techniques including observation, in-depth interviews, and documentation of key health worker informants. Data analysis was conducted using the Miles & Huberman interactive model, which includes word reduction, data presentation, and conclusion drawing. Results: The study results show that the KOPI PAHIT application is effective based on Campbell's five effectiveness indicators: program success, target success, program satisfaction, input and output suitability, and achievement of overall objectives. Implementation of this application can significantly reduce the prevalence of stunting from 28% in 2019 to 0.72% in 2025, while simultaneously increasing the ease of early detection, risk factor mapping, and nutrition education for the community. Therefore, challenges faced include limited digital literacy, unequal internet access, and the accuracy of self-measurement by the community. Novelty: This research focuses on a comprehensive analysis of the KOPI PAHIT app, a community-based digital innovation at the community health center level, proven effective in stunting prevention. These findings confirm that the use of digital technology can strengthen the national strategy to accelerate stunting reduction and has the potential to be replicated in other regions with similar conditions.